Training Management, Apparatus Competence, and Transformational Leadership on Employee Performance via Supervisory Capacity - Frimusandi Gebrial Talebong; Chablullah Wibisono; Sri Yanti (Goodwood Publishing, 2026)
Purpose: This study examines how training management, apparatus competence, and transformational leadership shape employee performance among maritime supervisory officers, and tests whether supervisory capacity functions as an intervening mechanism that converts these inputs into measurable performance outcomes at the Class II Sea and Shipping Guard Unit (UPT KPLP) of Tanjung Uban. Research Methodology: An explanatory quantitative design was applied using a saturated sampling technique that enrolled the entire population of 100 active officers. Data were gathered through a structured five point Likert questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS, covering outer model validity and reliability testing followed by inner model evaluation and bootstrapping with five thousand resamples. Results: Training management and apparatus competence significantly strengthen supervisory capacity, while transformational leadership shows no significant effect on either supervisory capacity or performance. Supervisory capacity significantly improves employee performance and partially mediates the training management to performance relationship while fully mediating the apparatus competence to performance relationship. Conclusions: Officer performance in high risk maritime oversight depends primarily on operational supervisory capacity rather than formal competence alone. Limitations: The study is confined to one unit with a modest sample and relies solely on internal officer perceptions. Contributions: The findings extend capacity building theory in high risk public sector maritime institutions and inform training policy design.